Discovering TV contents in a second screen app: perspectives from Portuguese and Brazilian markets - Abreu, Jorge Trinidad Ferraz de (2016)
The actual trends in the TV ecosystem present considerable social, organisational and technological challenges in the value-chain of Pay-TV operators. Among these is the global increase in bandwidth, the shifting of the storage capacity in the cloud, and the affordability of traditional content providers when facing the competitiveness of OTT content. In this framework, Pay-TV operators are presenting their customers with a huge offer of contents available from linear-TV, Catch-up TV and VoD services. However, this overloaded TV ecosystem is likely to lead viewers to get lost and face difficulties when deciding what to watch on TV. To overcome these difficulties and be competitive, operators need to provide innovative and trustable solutions, alternative to traditional EPGs, enabling users to discover the right content for a specific context. To target this problem, a second screen application (GUIDER) was developed to offer an original user interface, based on a multidimensional spatial representation of TV contents for those mindless zapping situations where viewers do not know, in advance, what they are in the mood to watch. This paper reports on the evaluation of the GUIDER App, aiming to determine the level of interest in the several features implemented and in the filtering criteria available; identify usability issues; and predicting the future uses of the App in domestic scenarios. The evaluation was made in Portugal and Brazil with a convenience sample of 20 participants in each country. Despite the differences in the TV ecosystems, both countries appear to be promising markets for this new kind of second screen applications, with Brazilians showing a higher perception of the added value of GUIDER.